1-Methylguanosine-Deficient tRNA of Salmonella enterica Serovar Typhimurium Affects Thiamine Metabolism - Björk, Glenn R. (American Society for Microbiology, 2003)
In Salmonella enterica serovar Typhimurium a mutation in the purF gene encoding the first enzyme in the purine pathway blocks, besides the synthesis of purine, the synthesis of thiamine when glucose is used as the carbon source. On carbon sources other than glucose, a purF mutant does not require thiamine, since the alternative pyrimidine biosynthetic (APB) pathway is activated. This pathway feeds into the purine pathway just after the PurF biosynthetic step and upstream of the intermediate 4-aminoimidazolribotide, which is the common intermediate in purine and thiamine synthesis. The activity of this pathway is also influenced by externally added pantothenate. tRNAs from S. enterica specific for leucine, proline, and arginine contain 1-methylguanosine (m(1)G37) adjacent to and 3′ of the anticodon (position 37). The formation of m(1)G37 is catalyzed by the enzyme tRNA(m(1)G37)methyltransferase, which is encoded by the trmD gene. Mutations in this gene, which result in an m(1)G37 deficiency in the tRNA, in a purF mutant mediate PurF-independent thiamine synthesis. This phenotype is specifically dependent on the m(1)G37 deficiency, since several other mutations which also affect translation fidelity and induce slow growth did not cause PurF-independent thiamine synthesis. Some antibiotics that are known to reduce the efficiency of translation also induce PurF-independent thiamine synthesis. We suggest that a slow decoding event at a codon(s) read by a tRNA(s) normally containing m(1)G37 is responsible for the PurF-independent thiamine synthesis and that this event causes a changed flux in the APB pathway.